An Instrumented Workstation to Evaluate Weight-Bearing Distribution in the Sitting Posture - Cristiane S. Moriguchi; Tatiana O. Sato; Helenice J.C.G. Coury (Elsevier, 2019)
Background: Sitting posture may be related to risk factors, including inadequate weight-bearing support, particularly when maintained for long periods. Considering that body weight is loaded in a closed support system composed of the seat, backrest, floor and working surface, the aims of the present study were to describe the development of an ergonomic sitting workstation to continuously record weight-bearing at the seat, chair, backrest, work surface, and floor and to test its measurement properties: reproducibility, criterion-related validity, and sensitivity. Methods: Rigid bodies (1 to 30 kg) and participant weights were recorded to evaluate the workstation measurement properties. Results: Rigid body tests showed variation values less than 0.050 kg on reproducibility test and errors below 5% of measured value on criterion validity tests. Participant tests showed no statistically significant differences between repeated measures (p ≥ 0.40), errors were less than 2% of participant weights and sensitivity presented statistically significant changes (p = 0.007). Conclusion: The sitting workstation proposed showed to be reliable, valid and sensitive for use in future ergonomic studies to evaluate the sitting posture. Keywords: Body weights, Ergonomics, Musculoskeletal disorders, Risk factors